Determinants of knowledge sharing using web technologies among students in higher education - Oyefolahan, Ishaq Oyebisi (Scientific Papers, 2014)
Knowledge sharing is becoming more and more important as such educational institutions are trying to harness this opportunity to students’ learning environment in order to create value.Therefore, the motivation behind this research is to conduct an empirical study to explore the factors that influence the success of knowledge-sharing using web technologies among students in higher education. A total number of 263 respondents were used in this study after removing the outliers from the actual data collected in International Islamic University Malaysia (IIUM). Based on the research model, multiple regression analysis was run on the group of constructs. The findings indicate benefit, experience, workgroup, knowledge culture, technology availability, and technology support were the significant variables that influence knowledge sharing using web 2.0 tools in the university. In this study, cost has no positive effect in influencing knowledge sharing using web technologies in the university.